Junior Cadets’ Perceptions on English as the Medium of Instruction in Maritime Education - Yayu Nopriani Martha (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Considering the global nature of the maritime industry, English proficiency is essential for effective communication, safety, and operational performance. This research employs a qualitative method using a structured questionnaire distributed to cadets of maritime education institutions. The data were analysed using descriptive statistics to measure the level of agreement, frequency, and overall perception of the respondents toward English-based instruction. The results show that the majority of cadets have a positive perception of English as the medium of instruction, with more than 70% of respondents agreeing that it enhances their understanding of technical subjects and improves their communication skills. However, approximately 30% of cadets reported challenges, including limited vocabulary, lack of confidence in speaking, and difficulty in understanding technical terminology. The study concludes that English as the medium of instruction is effective in supporting cadets’ academic and professional readiness. Nevertheless, additional language support programs and practical communication training are recommended to improve comprehension and confidence among cadets.